Engagement in Tobacco Use Prompting During Childhood or Adolescence and Its Association with Tobacco Use in Adulthood among Colombian Women - Isabel C Scarinci; Isabel C Garcés-Palacio (SAGE Publishing, 2020)
Although most tobacco users initiate this behavior before the age of 18, little is known about engaging in tobacco use prompting behaviors (TPBs) during childhood/adolescence and tobacco use in adulthood, particularly among women in low- and middle-income countries (LMICs). The purpose of this study was to examine engagement in TPBs during childhood or adolescence and tobacco use in adulthood among Colombian women and whether or not current/past tobacco users who were engaged in TPBs during their childhood or adolescence had more odds of engaging other children or adolescents in these behaviors as adults. There were 4262 adult women who were recruited and completed an interviewer-administered survey through a door-to-door approach across the 9 regions of Antioquia, Colombia using a multi-stage probabilistic sampling. TPBs were defined as someone being asked to: (1) empty an ashtray, (2) buy cigarettes, (3) put the cigarette in their mouth and light it, (4) light a cigarette without putting it in their mouth, or (5) smoke with the adult during childhood or adolescence. We conducted bivariate regression logistic models where variables with a P  < .25 were included in a parsimonious model. Approximately 40% of participants (41%) reported engaging in TPBs in childhood or adolescence. Buying cigarettes, lighting cigarettes with their mouth, and smoking with an adult were significantly associated with tobacco use in adulthood. Current/past tobacco users who reported being engaged in TPBs during childhood or adolescence (except for smoking with an adult) had higher odds of prompting these behaviors as adults. TPBs during childhood or adolescence are relevant contributors to tobacco use in adulthood among Colombian women.